ASSESSING ENTERPRISER PROFILES ON ENTREPRENEURIAL MANAGERIAL ACTIVITIES IN ELDORET, KENYA - Mwaniki, Mary Nyiva; Maket, Lydia (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this research is to analysis of enterpriser profiles on entrepreneurial managerial in Bungoma, Kenya .Efforts have been made to support entrepreneurial managerial activities training and the provision of consultative services; interestingly, the failure rate still remains high Neither research on the entrepreneur personality nor enterpriser profiles have demonstrated a decisive influence on entrepreneurial managerial activities. The study adopted a post-positivism research , with research design of explanatory survey .The target population and sample size were adopted from a thesis selected from Eldoret, Towns .Data was analyzed quantitatively using techniques such as: Multivariate analysis, structural equation modeling. Finding indicates: entrepreneurial competencies, mentoring, enterpriser profile and enterprise success dimensions were sufficiently reliable and valid to be included in the subsequent model testing. The measurement model results suggest that the model provides a reasonably good fit and thus it was suitable .The CFA results supported the measurement model.